Neuromuscular activity differs between the inside and outside legs during bend sprinting - Ohnuma, H.; Kumano, A.; Chiba, Y.; Yoshimoto, T. (Journal of Human Sport & Exercise, 2025)
This study aimed to clarify the characteristics of surface electromyograms during sprinting on a curved path. The participants were eighteen male track and field athletes including sprinters and hurdlers. Participants performed a 60-m sprint with maximal effort on straight and curved paths. Surface electromyogram signals were sampled from the biceps femoris, gluteus maximus, rectus femoris, vastus lateralis, medial head of gastrocnemius, and tibialis anterior, and kinematic variables and ground reaction forces were measured during sprinting. These variables were compared between straight and curved paths. Average rectified value of surface electromyograms for medial head of gastrocnemius in the inside leg on a curved path was greater than that on a straight path; however, there were no significant differences between the paths in the outside leg. In addition, there were no significant differences between paths. These results suggest that electromyographic strategies for performing curved sprinting with a large radius of curvature differ between the inside and outside legs and, that gastrocnemius muscle activity on inside leg contributes to force production during bend sprinting.